Martensite stabilization and thermal cycling stability of two-phase NiMnGa-based high-temperature shape memory alloys - Yang, Shuiyuan. (2013)
The martensite stabilization and thermal cycling stability of four types of two-phase NiMnGa-based high-temperature shape memory alloy, including Ni56+xMn25Ga19−x (x = 0, 1, 2, 3, 4), Ni56Mn25−yFeyGa19 (y = 4, 8, 9, 12, 16), Ni56Mn25−zCozGa19 (z = 4, 6, 8) and Ni56Mn25−wCuwGa19 (w = 2, 4, 8) alloys, were investigated. It is found that the martensite stabilization is closely related to the strength of the alloy and the volume fraction of γ phase; and increases as the alloy strength decreases. It is also found that in Ni56Mn25−yFeyGa19 alloys, with increasing Fe content to 12 and 16 at.%, the volume fraction of γ phase increases and the martensite stabilization decreases. The thermal cycling stability differs among different alloy systems and is related to the microstructural changes during thermal cycling and to the strength of the γ phase. Poor thermal cycling stability is observed in Ni56+xMn25Ga19−x (x > 0), Ni56Mn25−zCozGa19 and Ni56Mn25−wCuwGa19 alloys due to the formation of the ordered γ′ phase and the high strength of the γ phase. Results further show that Fe addition to Ni56Mn25Ga19 alloy can broaden the (bcc + γ) two-phase region and shift it to the Ni–Ga and Ni–Mn sides, hence stabilizing the two-phase region to lower temperatures. These effects can retard the formation of the ordered γ′ phase in the Ni56Mn25−yFeyGa19 system during thermal cycling, thus leading to good thermal cycling stability.